Processing ambiguity in a linguistic context: decision-making difficulties in non-aphasic patients with behavioral variant frontotemporal degeneration - Spotorno, Nicola; Healey, Meghan; McMillan, Corey T.; Rascovsky, Katya; Irwin, David J.; Clark, Robin; Grossman, Murray (Frontiers in Human Neuroscience, 2015)
Some extent of ambiguity is ubiquitous in every day conversations. For example, words have multiple meaning and very common pronouns, like “he” and “she” (anaphoric pronouns), have little meaning on their own and refer to a noun that has been previously introduced in the discourse. Ambiguity triggers a decision process that is not a subroutine of language processing but rather a more general domain resource. Therefore non-aphasic patients with limited decision-making capability can encounter severe limitation in language processing due to extra linguistic limitations. In the present study, we test patients with behavioral variant frontotemporal degeneration (bvFTD), focusing on anaphora as a paradigmatic example of ambiguity resolution in the linguistic domain. bvFTD is characterized by gray matter atrophy in prefrontal cortex, but relative sparing of peri-Sylvian cortex. A group of patients with parietal disease due to corticobasal syndrome (CBS) was also tested here in order to investigate the specific role of prefrontal cortex in the task employed in the current study. Participants were presented with a pair of sentences in which the first sentence contained two nouns while the second contained a pronoun. In the experimental (ambiguous) condition, both nouns are plausible referents of the pronoun, thus requiring decision-making resources. The results revealed that bvFTD patients are significantly less accurate than healthy seniors in identifying the correct referent of a pronoun in the ambiguous condition, although CBS patients were as accurate as healthy seniors. Imaging analyses related bvFTD patients’ performance to gray matter atrophy in ventromedial prefrontal cortex. These results suggest that bvFTD patients have difficulties in decision processes that involve the resolution of an ambiguity.